Jargon used by mechanic hold baggage screening in i gusti ngurah rai international airport - Hardiyana, Nina; Putra, I Gede Bagus Wahyu Nugraha; Ariyaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2022)
Jargon is a language variety containing a set of unique vocabulary that is used by the people who have the same interest, class (social status), or same position in the same area, for distance in the working area. The purpose of this study is to identify the form and the meaning of jargon used by Mechanic Hold Baggage Screening in I Gusti Ngurah Rai International Airport. This study uses qualitative methods by using field research. Descriptive study in textual analysis is applied in this study to analyze the form and meaning of jargon through the record of interview with the mechanics. It was analyzed by using the theory from Halingga (2004) that divided the form of jargon and the theory from Leech (1981) about the theory of meaning. The study concluded that there were 12 data (60%) for the word form, 3 data (15%) for the phrase form and 5 data (25%) for the abbreviated form. Acronyms are not used in this community. This percentage is proven if words, phrases and abbreviations are widely used in the data source.